Educational Applications For Children On Smart Phone Devices: A Lexical Study In A Computational Linguistics Perspective/ التطبيقات التعليمية للأطفال في أجهزة الهواتف الذكية دراسة معجمية في ضوء اللسانيات الحاسوبية - Nasef, Soaad Tharwat Mohamed; AlBattah, Aisha Nasser Saleh (Ijaz Arabi Journal of Arabic Learning, 2025)
The study aimed to reveal the importance of educational smartphone applications and their role in language acquisition and development in the educational process. In children’s acquisition of communication skills through audio-visual skills applications and the ability of these interactive applications in intelligent communication with children, The research also aimed to study these innovative educational applications through a lexical study in the light of computational linguistics and to reveal their importance in language acquisition and consolidation using visual and audio techniques. The research dealt with: (a lexical study of these applications through the (Integrated for Children in Arabic) application); he also studied audio-visual techniques and their role in creating lexical definitions in the application under study and studied electronic game design techniques and their role in creating lexical definition in the application under study. The research reached a set of results: the success of these applications depended mainly on providing the child with the opportunity for self-reliant learning without guidance, supervision, and traditional classes, which increases the child’s motivation toward learning. The application succeeded lexically in using modern lexical explanation methods appropriate for the childhood stage by employing many audio-visual multimedia. The application contains a group of digital dictionaries linked to an electronic dictionary network in a way that is easy for children to use. The application relied heavily on audio and video technologies (static and animated) and electronic linguistic games in the educational and entertaining process for the child.